Contribuição para a padronização química de Hancornia speciosa Gomes: desenvolvimento e validação de métodos analíticos para a quantificação de marcadores químicos - Ana Barbara Dias Pereira (2012)
Hancornia speciosa Gomes, a plant species popularly named mangaba, has ethnomedical uses to treat hypertension and diabetes, among others. The potential antihypertensive activity of the species has been previously described by our group employing in vitro, ex vivo and in vivo assays, rutin, L-(+)-bornesitol and quinic acid being regarded as the bioactive compounds. The goal of this work was to quantify the main constituents in extracts from H. speciosa leaves, aiming to contribute to their standardization. Analytical methods were developed and validated for this purpose. Definition of chemical markers for quantification was based on chemical fingerprint analyses of plant materials collected from different specimens. Chlorogenic acid, rutin, L-(+)-bornesitol, total flavonoids and FlavHS, a quercetin triglycoside identified by HPLC-MS analysis, were selected for quantitation. The contents of total flavonoids were assayed by spectrophotometry on UV-Vis, after chemical reaction with aluminum chloride. The method showed adequate linearity (r2 > 0.99), selectivity, precision (RSD < 3.09%), accuracy (recovery between 94.03% - 96.24%) and robustness. An HPLC-DAD method was developed and validated to quantify rutin, chlorogenic acid and FlavHS, which was shown to be linear (r2 > 0.9968), selective, precise (RSD < 2.65%), accurate (recovery between 97.09% - 102.97) and robust in the established conditions. HPLC with refractive index detector was evaluated to quantify L-(+)-bornesitol in matrices of H. speciosa; however, the established chromatographic conditions were not selective for quantitative analysis. As alternative, an HPLC-DAD method was developed to quantify this cyclitol in H. speciosa employing a derivatization step with p-toluenosulfonyl chloride and pentaerytritol as internal standard. The method presented adequate linearity (r2 > 0.9942), selectivity, precision (RSD < 3.17%), accuracy (recovery between 92.31% - 99.13%) and robustness. The developed methods were employed for the analysis of ethanol extracts from leaves of eight specimens, which showed significant differences in the contents of chemical markers. L-(+)-bornesitol was the major compound (5.77±0.09% to 8.78±0.14%), followed by total flavonoids (1.83±0.09% to 4.84±0.12%), rutin (1.05±0.00% to 2.00±0.03%), chlorogenic acid (0.80±0.01% to 1.52±0.02%) and FlavHS (0.32±0.001% to 0.84±0.00). The quantified compounds may be employed for standardization of derivatives from H. speciosa leaves.